2021
DOI: 10.3390/pr9040593
|View full text |Cite
|
Sign up to set email alerts
|

Fractionating of Lemongrass (Cymbopogon citratus) Essential Oil by Vacuum Fractional Distillation

Abstract: Lemongrass essential oil has many compounds appropriate for application in foods, cosmetics, and pharmaceutical products. Of these, citral is a high-value compound of interest to industry. This work aims to evaluate the use of vacuum fractional distillation to separate lemongrass essential oil compounds, producing essential oil fractions containing high citral content. The effect of process parameters, namely vacuum pressure, type column, and energy input, on the fractionation time, content, and recovery of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…The previously determined primary compositions of cinnamon essential oil and hydrosol (Ho et al, 2019;Huang et al, 2021;Michalczyk & Ostrowska, 2021;Yang, Liu, et al, 2021) and lemongrass hydrosol (Edris, 2009) were similar to the results observed in the present study. Conversely, cinnamyl acetate, aterpinenyl acetate, and a-terpineo have been reported in cinnamon hydrosol (Hamedi et al, 2017;Ho et al, 2019), while β-myrcene, αterpineol, limonene, and terpinene that were previously reported in lemongrass essential oil (Do et al, 2021;Kawhena et al, 2021) were not identified in the present study. The results of the comprehensive study could imply that the volatile chemical composition of hydrosols is dependent upon the raw material variety, collection time, extraction process, and determination method, and variations in these factors may have caused the differences observed in this study compared to those that were previously described.…”
Section: Volatile Chemical Composition Of the Ccph And Ccshcontrasting
confidence: 70%
“…The previously determined primary compositions of cinnamon essential oil and hydrosol (Ho et al, 2019;Huang et al, 2021;Michalczyk & Ostrowska, 2021;Yang, Liu, et al, 2021) and lemongrass hydrosol (Edris, 2009) were similar to the results observed in the present study. Conversely, cinnamyl acetate, aterpinenyl acetate, and a-terpineo have been reported in cinnamon hydrosol (Hamedi et al, 2017;Ho et al, 2019), while β-myrcene, αterpineol, limonene, and terpinene that were previously reported in lemongrass essential oil (Do et al, 2021;Kawhena et al, 2021) were not identified in the present study. The results of the comprehensive study could imply that the volatile chemical composition of hydrosols is dependent upon the raw material variety, collection time, extraction process, and determination method, and variations in these factors may have caused the differences observed in this study compared to those that were previously described.…”
Section: Volatile Chemical Composition Of the Ccph And Ccshcontrasting
confidence: 70%
“…Therefore, a high vacuum was preferred during the present study to reduce the temperature of vaporization of the volatile mixture. Studies on the fractional distillation of EO are rare although this process is very common in the petrochemical industry [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two different processes were used to isolate fractions from the EO. In the first, high vacuum (−760 mmHg) fractional distillation was used to isolate three different constant boiling fractions along with the residue [ 8 ]. In the second, EO was slowly cooled to −50 °C using a lyophilizer (model BL-10B, Bioland, Shaanxi, China) to isolate two fractions (crystalline and non-crystalline fractions).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cymbopogon citratus (DC.) Stapf (C. citratus) or lemongrass is an herbaceous plant of the Poaceae family growing in humid tropical areas which is mainly cultivated for its stems and leaves whose infusion gives a tea with strong lemony odor due to its high content of the aldehyde citral [33]. Muala et al [34].…”
mentioning
confidence: 99%